MENINGKATKAN PEMAHAMAN MATERI POLA GERAK DASAR SISWA KELAS II MENGGUNAKAN MEDIA SIRKUIT N-LOKOMOTIF DI SDN AIRLANGGA I SURABAYA - Al Basri, Muhammad Rizki; Andrijanto, Dony; Aidin, Luthfi (Jurnal Dedikasi Pendidikan, 2025)
This study aims to improve students' understanding of basic movement patterns by utilizing the N-Locomotive Circuit learning media. The study was conducted at SDN Airlangga I, Surabaya City, involving 29 students as samples. Basic movement patterns are the basis of movement that is the foundation for more complex movement agility. The research method used is Classroom Action Research (CAR) with data collection through interviews, observations, and tests. The results of the study showed that the average understanding of students in the pre-action was 66.82%. In cycle I, the average increased to 68.34%, and in cycle II it reached 80.24%. This increase exceeded the Minimum Completion Criteria (KKM) of 70, indicating that the N-Locomotive Circuit learning media is effective in improving student learning outcomes and encouraging better cooperation in class